ESP: Cancellation of Academic and Occupational Purposes? - Gumovskaya, Galina (Advances in Social Sciences Research Journal, 2024)
Changes in education and the needs of the educational space lead to changes in the norms and methods of educational processes, and as a result it turns out that new methods cancel out the old ones. Thus, the concept and methodology of teaching languages for special (professional) purposes since 1978, has been recognized worldwide as innovative and relevant for specialized vocational training of schoolchildren and youth [23]. Today, the idea of LSP has become irrelevant, according to the initiators themselves Tom Hutchinson and Alan Waters [24], and should be displaced from school disciplines into the service industry to meet the needs of specialists of other profiles. But the case should be presented in its historical perspective. To get better understanding of the unpleasant aftertaste of the initiators’ decision, we should refer to most prominent linguists of the world who contributed greatly to the development of the LSP idea in the world. An overview of the rise and fall of the idea and methods of languages for specific purposes is outlined in the book “LSP: English of Professional Communication” by Galina Gumovskaya [19].